Financial Innovation and Fragility - Fabian Kühnhausen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
In this paper, I evaluate the impact of innovative activity of financial agents on their fragility in a competitive framework. There exist a vast array of concerns about the interconnection of financial innovations, financial distress of firms and financial crises provided by theoretical arguments. I build on these and assess empirically the causal link between a financial agents' innovativeness and stability. Using a unique data set on financial innovations in the USA between 1990 and 2002, I show that a larger degree of innovation negatively (positively) affects firm stability (fragility) after controlling for the underlying firm characteristics. The results are robust against different modifications of innovation measures and against different fragility parameters indicating profitability, activity risk and risk of insolvency.
urn:nbn:de:bvb:19-epub-21173-5
Keywords: G01; G2; L11; O31; 330; Incentives to Innovate; Financial Innovation; Fragility